PENGARUH RENDAHNYA TINGKAT KEPUASAN KONSUMEN, HARGA, DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PERPINDAHAN MEREK PONSEL SONY ERICSSON KE PONSEL CHINA (Studi Pada Siswa Siswi SMA IBU KARTINI Kota Semarang) - Akbar Wibawanto, Rindiet; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2012)
In the development of business area, recently has peeped out a symptom, where companies supplied many variances of product at the same industry. The competitiveness of products between producers might lead to customer’s brand switching. One of the way to maintain the current customers is by improving the customer’s satisfaction. At this time there are many cheaper products but having competitive design and facilities. Promotion through advertisement or other media by using celebrity endorser can also become fascination point to influence the customers in brand switching, through image, their appearance, words, etc. The purpose of this study to analyze the effect of low levels of customer satisfaction, pricing, and celebrity endorser of the brand switching decisionsThe method of data collection used a questionnaire with the sampling technique used purposive sampling technique. The method of analysis used in this study were multiple linear regression analysis, using SPSS program. The analysis showed low levels of consumer satisfaction has a positive effect on brand switching decision. The price of making a positive influence on brand switching. Celebrity endorser positive effect on brand switching. These results indicate that the company should be able to create products consumers desire compliance, lower prices than competitors, and the selection of right brand ambassador because of the low levels of customer satisfaction, pricing and celebrity endorser brand shown to affect migration decisions.